The Empirical Performance of Orthodox Models of the Firm: Conventional Firms and Worker Cooperatives - Pencavel, John; Craig, Ben (Journal of Political Economy, 1994)
Though it is routinely posited that organizations with different property rights will not exhibit the same responses to changes in their economic environment, compelling evidence of such behavior is difficult to find. We collected observations on two types of firms–conventional proprietorships and worker-owned cooperatives–operating in the same industry, in the same location, and at the same period of time. We compare the firms' reactions to changes in their input and output prices and ask whether their reactions are consistent with orthodox models of profit and dividend maximization.